Current clinical standards for renal transplantation: a survey among urological and surgical transplantation centers in Germany - Müller, Laura; Apel, Hendrik; Peters, Robert; Friedersdorff, Frank; Kernig, Karoline; Zeuschner, Philip; Stöckle, Michael; Putz, Juliane; Huber, Johannes; Flegar, Luka (World journal of urology, 2025)
Purpose: Kidney transplants in Germany are either performed by surgical, urological or interdisciplinary teams. Hence, perioperative details might differ in relevant ways. The aim of our survey was to record and compare the respective perioperative standards. Methods: A structured 50-item questionnaire was sent via email to all certified German kidney transplant centers (n = 38). Anonymized data collection was performed with www.surveymonkey.com from November 2023 - May 2024. Results: Complete responses were obtained from 34/38 centers (response rate 89.5%); 13 were urological-led and 21 surgical-led programs. In most cases (76% urological vs. 90% surgical, n = 10 and 19), transplantation is performed extraperitoneally via hockey-stick incision. A peritoneal fenestration for lymphocele prophylaxis is not performed routinely (69% vs. 86%, n = 9 and 18). Vascular anastomoses are primarily frequently sutured with 5 − 0 or 6 − 0 prolene, and the ureteral anastomosis with 4 − 0, 5 − 0 or 6 − 0 PDS suture. The Lich-Gregoir technique is most commonly used for ureteral implantation (84% in urology vs. 76% in surgery, p = 0,55). There are only small differences in postoperative management between urological and surgical programs, e.g. regarding the duration of catheterization (7–10 days vs. < 7 days; p = 0.008) or the time of discharge (10–14 days vs. 6–8 days; p = 0,05). Conclusion: The majority of kidney transplants in Germany is performed according to similar standards. There are minor differences in the specialists approach, e.g. in the choice of suture material. Certain practices, such as peritoneal fenestration for lymphocele prophylaxis, warrant further scientific evaluation.
Veröffentlicht: 20. November 2025
Gesehen am 29.01.2026